MEMPERKUAT SISTEM PENGENDALIAN MANAJEMEN PERUSAHAAN MELALUI TATA KELOLA BAIK - Azka, Aditya Fadillah; Harahap, Ludwina (Universitas Trilogi, 2023)
Management control and good governance are two concepts that are interrelated and mutually supportive. Management control is an important process in maintaining company performance and effectiveness, while good governance plays an important role in maintaining integrity and transparency in controlling company management. This study uses the literature study method to analyze the relationship between good governance and management control. The results show that there are two important aspects in strengthening the company's management control system through good governance, namely increasing transparency and reporting, as well as increasing accountability and risk management. Good transparency in financial and operational reporting allows management to effectively monitor company performance and identify problems quickly. Meanwhile, strong accountability helps reduce errors, abuse, and risks associated with company operations. Keywords: Accountability; Management Control; Good Governance; Reporting; Risk; Transparency